Research on the Path of Strengthening the Construction of Professional Ethics and Conduct for College Teachers in the New Era - Zhang, Chanjun (Journal of Theory and Practice of Social Science, 2023)
At present, with the continuous progress of China's education development level, the country and people have put forward higher requirements for the development of the education industry. Basic education and higher education together constitute a complete education system in China. Higher education plays a significant role in cultivating talents and improving their comprehensive qualities, and university teachers also play a significant role in this process. Therefore, strengthening the construction of university teachers' professional ethics and conduct is crucial. This article will focus on the topic of "Strengthening the Construction of Professional Ethics and Conduct for College Teachers in the New Era".